INFLUENCE OF BUDGETING AND DEBT MANAGEMENT LITERACY TRAINING ON FINANCIAL PERFORMANCE OF EQUITY BANK TRAINED WOMEN SELF HELP GROUPS IN MACHAKOS TOWN, KENYA - Mberia, Charity; Wachira, Kevin (International Journal of Entrepreneurship and Project Management, 2021)
Purpose: The purpose of the study was to find out the influence of financial literacy on budgeting and debt management skills on financial performance of Equity bank trained women self-help groups in Machakos Town, Kenya. Methodology: The research methodology employed two theories namely; The Bruce Tuckman's Theory of group development and Expectancy Theory. Empirical studies were outlined and existing literature critiqued hence the research gap. The target population was 33 women self-help groups that are registered and trained by Equity Bank. Census sampling design was used for accuracy of the subdivisions of the subdivision and purposive sampling technique was used to calculate sample size because it focuses on particular characteristics of a population. The study used structured questionnaire as its data collection instrument. Analyzed data was presented through graphs and charts. Results: Findings on budget training established a significant relationship between budget training and financial performance of women self-help groups in Machakos Town, r=0.255, p=0.035<0.05 indicating that adding a unit on budget training will increase financial performance of women self-help groups in Machakos Town by 0.255 multiple units. Further findings on debt management skills training established a significant relationship between debt management training skills training and financial performance of women self-help groups in Machakos Town, r=0.600, p=0.005<0.05 indicating that adding a unit on debt management training skills will increase financial performance of women self-help groups in Machakos Town by 0.600 multiple units.